Marine conservation: linking taxonomy, Red Listing, and public engagement - Torben Riehl; Monika Böhm; Simone N. Brandão; Angelika Brandt; Chong Chen; Gregory D. Edgecombe; Hosea J. ‶Ze″ Frank; Austin J. Gallagher; Rebecca Goldburg; Pat Hutchings; Fabrizio M. Machado; Volker Mosbrugger; et al. (Trends in Ecology & Evolution, 2026)

Diet composition of data‐limited marlins ( Istiophoridae ) in the Northwest Atlantic - Joseph J. Dello Russo; John M. Logan; Riley Austin; Zachary T. Whitener; Isabelle Sée; Benjamin M. Hurley; Lisa A. Kerr; Joseph M. Quattro; Walter J. Golet (Journal of Fish Biology, 2026)
Knowledge of the dietary composition of Atlantic marlins, especially for recently acknowledged species such as roundscale spearfish ( Tetrapturus georgii ), is limited, as sample access is constrained by international quotas and intermittent landing rates. A series of annual offshore recreational fishing tournaments target Atlantic blue marlin ( Makaira nigricans ), white marlin ( Kajikia albida ) and roundscale spearfish on their seasonal foraging grounds in the South and Mid‐Atlantic Bight. Through this network of tournaments and recreational anglers, we collected stomachs from Atlantic blue marlin ( n = 32), white marlin ( n = 35) and roundscale spearfish ( n = 44) from 2018 to 2020 to investigate general diet composition. Stomach content analysis and DNA barcoding identified a total of 16 prey families across the three focal species, but the majority of prey weight (%W) was from two families (Scombridae and Ommastrephidae). Blue marlin and roundscale spearfish were predominantly piscivorous (99.0 and 80.6%W fishes, respectively), whereas white marlin mainly consumed cephalopods (80%W). The contribution of Scombridae was highest for blue marlin (94.6%W), intermediate for roundscale spearfish (51.7%W) and lowest for white marlin (11%W), with an inverse pattern of relative contribution for Ommastrephidae (0.9, 16.1 and 73.9%W, respectively). Roundscale spearfish and white marlin, despite having a near identical morphology, had diets composed of different prey types in our sample. These dietary data, from three epipelagic apex predators, provide important information for wider ecosystem‐based studies, including in relation to the Mackerel, Squid and Butterfish Fishery Management Plan overseen by the Mid‐Atlantic Fishery Management Council.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Nuanced effects of relative body size on social motivation in a highly gregarious catfish - Arne Jungwirth; Jesse N. Kern; Munir Siddiqui; Austin Chiang; Natalie Eisen; Ethan Lac; Gerald Wilkinson; Riva J. Riley (Behavioural Processes, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Investigating the relationship between abiotic factors and the behaviour of an All-Male Nile crocodile (Crocodylus niloticus) Group - Austin Leeds; Alex Riley; Laura Stalter; Megan Terry; Andrew C. Alba; Joseph Soltis (Applied Animal Behaviour Science, 2024)

Lessons for conservation from beneath the pavement - Alexis M. Mychajliw; Elizabeth R. Ellwood; Peter S. Alagona; R. Scott Anderson; Mairin A. Balisi; Eric Biber; Justin L. Brown; Jessie George; Austin J. W. Hendy; Lila Higgins; Courtney A. Hofman; Ashley Leger; et al. (Conservation Biology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.